A Series of 2‐((1‐Phenyl‐1H‐imidazol‐5‐yl)methyl)‐1H‐indoles as Indoleamine 2, 3‐Dioxygenase 1 (IDO1) Inhibitors. (26th May 2021) - Zheng, Yong; Stafford, Paul M.; Stover, Kurt R.; Mohan, Darapaneni Chandra; Gupta, Mayuri; Keske, Eric C.; Schiavini, Paolo; Villar, Laura; Wu, Fan; Kreft, Alexander; Thomas, Kiersten; Raaphorst, Elana; et al.
Abstract: Indoleamine 2, 3‐dioxygenase 1 (IDO1) is a promising therapeutic target in cancer immunotherapy and neurological disease. Thus, searching for highly active inhibitors for use in human cancers is now a focus of widespread research and development efforts. In this study, we report the structure‐based design of 2‐(5‐imidazolyl)indole derivatives, a series of novel IDO1 inhibitors which have been designed and synthesized based on our previous study using N 1‐substituted 5‐indoleimidazoles. Among these, we have identified one with a strong IDO1 inhibitory activity (IC50 =0.16 μM, EC50 =0.3 μM). Structural‐activity relationship (SAR) and computational docking simulations suggest that a hydroxyl group favorably interacts with a proximal Ser167 residue in Pocket A, improving IDO1 inhibitory potency. The brain penetrance of potent compounds was estimated by calculation of the Blood Brain Barrier (BBB) Score and Brain Exposure Efficiency (BEE) Score. Many compounds had favorable scores and the two most promising compounds were advanced to a pharmacokinetic study which demonstrated that both compounds were brain penetrant. We have thus discovered a flexible scaffold for brain penetrant IDO1 inhibitors, exemplified by several potent, brain penetrant, agents. With this promising scaffold, we provide herein a basis for further development of brain penetrant IDO1 inhibitors. Abstract : Desiging IDO1 inhibitors : We present herein the structure‐based design of novel 2‐(5‐imidazolyl)indole derivatives which have been devised based on our previous study on N 1‐substituted‐5‐indoleimidazoles in our search of indoleamine 2, 3‐dioxygenase 1 (IDO1) inhibitors, a promising therapeutic target in cancer immunotherapy and neurological diseases. We were able to design and synthesize a series of 2‐(5‐imidazolyl)indole derivatives and we evaluated their biological activity. As a result, we identified a compound showing a good IDO1 inhibitory activity. We also predicted the brain penetrance of these compounds using the Blood Brain Barrier (BBB) Score and Brain Exposure Efficiency (BEE) Score. PK studies were performed for the most promising compounds which confirmed their brain penetrance.